ANALISIS KEBERLANJUTAN PENGELOLAAN TANAMAN PADI PRODUK REKAYASA GENETIK DI JAWA BARAT DAN JAWA TIMUR - Puspita Deswina; Rizal Syarief; Latief M Rachman; M Herman (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2015)
ABSTRACT Sustainability Analysis of Genetically Engineered Rice Management in West Java and East Java Province. Bt rice genetically engineered plants (GEPs) having endurance to stem borer insect was developed by the Research Center for Biotechnology LIPI. Compared to conventional plants, the GEP has to obtain a certificate of biosafety and food safety before being released and used by public. It is necessary to study the sustainability of GEP based on indications of sustainable development. The research objective was to determine the sustainability of Bt rice plant based on attributes that construct the dimensions of ecological, economic, social, technological and institutional law. Analysis of the data used Multi Dimensional Scaling (MDS), and the results were expressed in the index form of sustainable management of GEP. Results of the study showed that the sustainability of multidimensional GEP Bt rice corresponds to the criteria of fair with the value 58.99%, except for the technological dimension with the value of 46.71%, which was classified as less sustainable. In addition, lists of value for other dimensions are: 73.02% for environmental dimension, 69.3% for economic dimension, 51.22% for social dimension, 54.74% for institution and law dimension, and 46.71% for technology dimension that was on less sustainable value. The results also showed ten leverage factors that might affect the increasing the sustainability index of all dimensions. These factors are: environmental dimensions (possibility of crossing genetic materials from GE crops to non-GE crops), economic dimensions (farmers dependency to GE crops, affordable price of GEP seed), social dimensions (informations of GEP, public perception and acception, public participation in decision making), technology dimensions (number of GE plants from internal R&D, capacity building in research and assessment of GEP), institutions and law dimensions (implementation of regulations, GEP labelling). Keywords: Genetically Engineered Plants (GEPs), biosafety, sustainability, Bt Rice ABSTRAK Tanaman padi Bt Produk Rekayasa Genetik (PRG) memiliki sifat ketahanan terhadap hama penggerek batang kuning, hasil pengembangan Puslit Bioteknologi LIPI. Berbeda dengan tanaman konvensional, tanaman PRG harus memperoleh sertifikat keamanan hayati dan keamanan pangan sebelum dilepas dan dimanfaatkan oleh masyarakat. Kajian keberlanjutan PRG berdasarkan indikasi pembangunan berkelanjutan telah dilakukan menggunakan metode expert survey dan pemilihan responden dari kalangan pakar di wilayah Jawa Barat dan Jawa Timur. Tujuan penelitian adalah mengetahui keberlanjutan tanaman Padi Bt PRG berdasarkan atribut-atribut yang menyusun dimensi ekologi, ekonomi, sosial, teknologi serta hukum kelembagaan. Analisis data yang digunakan adalah Multi Dimensional Scaling (MDS) yang hasilnya dinyatakan dalam bentuk indeks keberlanjutan terhadap setiap dimensi yang dikaji. Hasil kajian terhadap multidimensi keberlanjutan tergolong pada kriteria cukup berkelanjutan dengan nilai 58,99%, kecuali untuk dimensi teknologi dengan nilai 46,71% yang tergolong kurang berkelanjutan. Nilai keberlanjutan untuk dimensi lingkungan 73,02%, dimensi ekonomi 69,30%, dimensi sosial 51,22% dan dimensi hukum kelembagaan 54,74%. Diperoleh sepuluh faktor pengungkit (leverage factor) yang dapat mempengaruhi peningkatan indeks keberlanjutan yaitu dari dimensi ekologi (Kemungkinan terjadinya perpindahan (crossing) material genetik dari tanaman PRG ke tanaman non-PRG), dimensi ekonomi (Ketergantungan petani pada tanaman PRG, Harga beli benih PRG yang terjangkau), dimensi sosial (persepsi dan penerimaan masyarakat, keterlibatan publik dalam pengambilan keputusan), dimensi teknologi (jumlah tanaman PRG hasil litbang sendiri, kemampuan SDM melakukan riset dan pengujian tanaman PRG) serta dimensi hukum kelembagaan (implementasi peraturan dan undang-undang, labeling terhadap PRG).Kata kunci: Produk Rekayasa Genetik (PRG), keamanan hayati, keberlanjutan (sustainability), padi Bt